CHOOSING PHYSICS AS A SPECIALIZATION IN GRADUATE STUDIES: VIEWS AND FACTORS AFFECTING IT - Mae Anne Regero Migue (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
Physics is one of the complex science subject and students taking tertiary science education courses do not choose physics as their specialization. The Philippine Normal University was also experiencing the same, only few graduate students choose the said subject as a specialization. With this, the researcher seeks to find out the views and factors affecting the situation. The data shows that the p-value calculated for the negative views towards Physics as well as factors affecting it is less than (